2015
DOI: 10.1007/s00432-015-1966-6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha polymorphisms and the risk of prostate cancer development

Abstract: The present study suggests that rs2077647 polymorphism may be a risk factor for prostate cancer especially in patients diagnosed before the age of 60, while rs3798577 polymorphism could probably serve rather as promoting factor in combination with other polymorphisms in estrogen receptor alpha contributing preferably to development of high-grade carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Figure 3 summarises the difference in ERα and ERβ expression between non-cancerous and cancerous prostate tissue. Single nucleotide polymorphisms (SNPs) in the ER genes have been investigated and associations have been made between certain polymorphisms and the risk of prostate cancer (Holt et al 2013, Jurečeková et al 2015. In both studies, the genomes from histologically confirmed human prostate cancer samples were analysed using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP)-based analysis and compared with age-matched healthy control subjects.…”
Section: Oestrogen Receptors (Er) In the Prostatementioning
confidence: 99%
“…Figure 3 summarises the difference in ERα and ERβ expression between non-cancerous and cancerous prostate tissue. Single nucleotide polymorphisms (SNPs) in the ER genes have been investigated and associations have been made between certain polymorphisms and the risk of prostate cancer (Holt et al 2013, Jurečeková et al 2015. In both studies, the genomes from histologically confirmed human prostate cancer samples were analysed using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP)-based analysis and compared with age-matched healthy control subjects.…”
Section: Oestrogen Receptors (Er) In the Prostatementioning
confidence: 99%